(untitled) - Maxwell, John C. (Nashville, 2007)
While a few people appear to be born leaders, the ability to lead is actually a collection of skills, nearly all of which can be learned and sharpened. Based on his New York Times bestseller The 21 Irrefutable Laws of Leadership, author John C. Maxwell presents a daily plan to help you grow as a leader in your personal, professional, and spiritual life.
Keywords: Khả năng lãnh đạo,Khả năng lãnh đạo,Leadership,Leadership,Professional ethics; Khía cạnh tôn giáo,Religious aspects